Elastisitas Kesempatan Kerja Sektoral di Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study is to determine how much influence and elasticity of the variable GDP on the Employment Opportunities Primary Sector, Secondary Sector and Tertiary Sector in Samarinda. This study uses time series data period 2006 - 2013 and use the Simple Linear Regression analysis tool with software SPSS 21.0. the study found GDP Has significant impact on Employment Opportunities Primary Sector, Secondary Sector and Tertiary Sector. Results from the study showed that the coefficient of Employment Opportunities Primary Sector is 1.89 which means that every 1% change in the value of GDP cause Employment Opportunities Primary Sector changed for 1.89% Employment Opportunities Primary Sector is elastic or Ekk> 1. Coefficient of Employment Opportunities coefficient Secondary Sector is 1.39 which means that every 1% change in the value of GDP cause Employment Opportunities Secondary Sector changed for 1.39% Employment Opportunities Secondary Sector is Elastic or Ekk> 1. The coefficient Employment Opportunities Tertiary Sector is 0.98 which means that every 1% change in the value of GDP cause Employment Opportunities Tertiary Sector changed for 0.98% Employment Opportunities Tertiary Sector is Inelastic or Ekk <1.Keywords: Employment and Economic Sectors